Delay Effects on Consensus-Based Distributed Economic Dispatch Algorithm in Microgrid - Chen, Gang; Zhao, Zhongyuan (IEEE transactions on power systems, 2018)
For microgrids with connected but sparse communication networks, consensus-based approach can provide a distributed solution to the economic dispatch problem. However, as time delays in communication networks are nonnegligible, performances of consensus-based distributed economic dispatch algorithms are not well disclosed and investigated. Considering the effects of time delays, we first provide a novel consensus-based economic dispatch algorithm. The algorithm is fully distributed such that the optimal dispatch of energy resources in microgrid can be implemented in a distributed manner. The influence of time delays on distributed economic dispatch is strictly analyzed. The maximum allowable delay bounds are derived by applying the generalized Nyquist criterion. Several simulations are presented to verify the effectiveness of the algorithm and the correctness of the theoretical results.